Faktor – faktor yang Mempengaruhi Pandemic Incubation Program (PIP) terhadap Keberlanjutan Usaha Mikro, Kecil dan Menengah di Kota Denpasar - I Gede Bagus Dera Setiawan; Ni Wayan Purnama Rusadi; Desak Made Indah Paramitha Sari (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2021)
The current Covid-19 pandemic has certainly weakened various economic sectors throughout the world, including in Bali, where the tourism sector is the main source of income for the community. As of April 13, 2020, the number of laid-off employees has reached 800 and 46,000 employees have been laid off. Most of them are employees in the tourism sector such as hotels and restaurants. Along with the increasing corona outbreak, the number of employees who have been laid off is increasing. On May 12, 2020, the number reached 2,189 people, while 65,594 employees were laid off. The high number of workers who were economically affected by the Pandemic in Denpasar City prompted the Denpasar City Government through the Denpasar City Tourism Office (DISPAR) to hold a Pandemic Incubation Program. This program is expected to be a solution to find other sources of income by building micro, small and medium enterprises. This study discusses the perceptions of participants and the factors that influence the PIP program on the sustainability of micro, small and medium enterprises in Denpasar City. The method used in this research is quantitative descriptive analysis, using the SEM-PLS analysis method. The sample in this study amounted to 105 participants who were selected purposively with the criteria of participants participating in the PIP program from start to finish for two months. The perception of PIP program participants is in the good category with a score of 3.66; while the participant's perception of the sustainability of micro, small and medium enterprises in Denpasar City got a score of 3.47 which is also included in the good category. The results of the analysis also show that the PIP program has a positive and significant relationship with the continuation of micro, small and medium enterprises in Denpasar City.